Does soil amended with biochar and hydrochar reduce ammonia emissions following the application of pig slurry?. (14th October 2015) - Subedi, R.; Kammann, C.; Pelissetti, S.; Taupe, N.; Bertora, C.; Monaco, S.; Grignani, C.
Summary: Combining amendments to the soil made by biochar or hydrochar with nitrogen (N) fertilizer can modify soil N dynamics and availability. Such a response suggests that these amendments would affect ammonia (NH3 ) emissions from slurry similarly, and potentially reduce volatilization of NH3 . This study measured the potential emissions of NH3 following application of pig slurry to the surface of silt‐loam and loam soils amended with biochar and hydrochar (both derived from Miscanthus × giganteus (Greef et Deu)) at a rate of 3% soil dry weight (16 t ha −1 soil area, on average) and 60% water‐filled pore space (WFPS). The experiment was carried out in a dynamic chamber connected to a photo‐acoustic trace gas analyser in a controlled climate (20°C) for 48 hours. Statistically significant differences ( P < 0.05) in total emissions were observed between both treatment and soil types. Surprisingly, both amendments increased emissions of NH3 compared with the control; cumulative NH3 emissions averaged 38.7 and 23.5% of applied total ammonium nitrogen (TAN) for hydrochar and biochar, respectively, whereas it was 18.2% for the control. The larger emissions in hydrochar‐amended soil were attributed to the reduced ability to absorb NH4 + associated with greater hydrophobicity and strong pH buffering of the slurry. Furthermore, final soil analyses with deionised water extracts showed significant differences ( P < 0.05) in mineral N concentration between treatments. The smaller ammonium concentrations in biochar‐amended soil suggest that some NH4 + ‐N was immobilized by adsorption on to biochar surfaces. This study observed that biochar and hydrochar properties, as well as soil characteristics, play important roles in controlling NH3 emissions from surface slurry applications. The results obtained identified circumstances where these amendments even enhance volatilization, which provides new information on and insight into the extent and limitations of the potential of biochar and hydrochar for the mitigation of emissions.